Motivation in the practice of insurance companies. (Journal of Economic Research & Business Administration, 2016)
In today’s world, motivation plays an important role in personnel management and determines the possibility of the formation of effective management. The problem of motivation plays an important role in the management of both the theoretical and practical aspects. The definition of motivation as a major management functions formulated M.H. Meskon «motivation – process motivations themselves and others in the activities in order to achieve personal and organizational goals.» In the area of management control is a function consisting in shaping the motivation of employees to work. This article discusses the methods and forms of the organizational structure of the insurance companies ‘management, new approaches to solving the problem of motivation and stimulation of labor, determined by the value and the importance of motivation in the insurance companies’ management practice, it is a model of motivational process, examines the five largest insurance Kazakhstan companies, the success of which motivation He played a major role.
Keywords: motivation; management; personnel; personnel management; insurance.